Discerning congregational growth : a case study - Vineyard Christian Fellowship Tygerberg, 1992-2000 with special reference to leadership - Goddard, C. R. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2001.